High-resolution phylogeography of zoonotic tapeworm Echinococcus granulosus sensu stricto genotype G1 with an emphasis on its distribution in Turkey, Italy and Spain - Kinkar, Liina; Laurimae, Teivi; Simsek, Sami; Balkaya, Ibrahim; Casulli, Adriano; Manfredi, Maria Teresa; Saarma, Urmas (Cambridge Univ Press, 2016)
Echinococcus granulosus is the causative agent of cystic echinococcosis. The disease is a significant global public health concern and human infections are most commonly associated with E. granulosus sensu stricto (s. s.) genotype G1. The objectives of this study were to: (i) analyse the genetic variation and phylogeography of E. granulosus s. s. G1 in part of its main distribution range in Europe using 8274 bp of mtDNA; (ii) compare the results with those derived from previously used shorter mtDNA sequences and highlight the major differences. We sequenced a total of 91 E. granulosus s. s. G1 isolates from six different intermediate host species, including humans. The isolates originated from seven countries representing primarily Turkey, Italy and Spain. Few samples were also from Albania, Greece, Romania and from a patient originating from Algeria, but diagnosed in Finland. The analysed 91 sequences were divided into 83 haplotypes, revealing complex phylogeography and high genetic variation of E. granulosus s. s. G1 in Europe, particularly in the high-diversity domestication centre of western Asia. Comparisons with shorter mtDNA datasets revealed that 8274 bp sequences provided significantly higher phylogenetic resolution and thus more power to reveal the genetic relations between different haplotypes.
Keywords: cystic echinococcosis; high genetic variability; hydatid disease; mitochondrial genome; mtDNA; sheep domestication; zoonosis; zoonotic pathogens